Identification of creatine kinase and alpha‐1 antitrypsin as protein targets of alkylation by sulfur mustard. Issue 2 (18th September 2020) - Lüling, Robin; Schmeißer, Wolfgang; Siegert, Markus; Mückter, Harald; Dietrich, Alexander; Thiermann, Horst; Gudermann, Thomas; John, Harald; Steinritz, Dirk
Abstract: Sulfur mustard (SM) is a toxic chemical warfare agent deployed in several conflicts within the last 100 years and still represents a threat in terroristic attacks and warfare. SM research focuses on understanding the pathophysiology of SM and identifying novel biomarkers of exposure. SM is known to alkylate nucleophilic moieties of endogenous proteins, for example, free thiol groups of cysteine residues. The two‐dimensional‐thiol‐differences in gel electrophoresis (2D‐thiol‐DIGE) technique is an initial proteomics approach to detect proteins with free cysteine residues. These amino acids are selectively labeled with infrared‐maleimide dyes visualized after GE. Cysteine residues derivatized by alkylating agents are no longer accessible for the maleimide–thiol coupling resulting in the loss of the fluorescent signal of the corresponding protein. To prove the applicability of 2D‐thiol‐DIGE, this technology was exemplarily applied to neat human serum albumin treated with SM, to lysates from human cell culture exposed to SM as well as to human plasma exposed to CEES (chloroethyl ethyl sulfide, an SM analogue). Exemplarily, the most prominent proteins modified by SM were identified by matrix‐assisted laser desorption/ionization time‐of‐flight (tandem) mass spectrometry, MALDI‐TOF MS(/MS), as creatine kinase (CK) from human cells and as alpha‐1 antitrypsin (A1AT) from plasma samples. Peptides containing the residue Cys 282 of CK and Cys 232 of A1AT were unambiguously identified by micro liquid chromatography‐electrospray ionization high‐resolution tandem‐mass spectrometry (μLC‐ESI MS/HR MS) as being alkylated by SM bearing the specific hydroxyethylthioethyl‐(HETE)‐moiety. Both peptides might represent potential biomarkers of SM exposure. This is the first report introducing these endogenous proteins as targets of SM alkylation. Abstract : Using the two‐dimensional‐thiol‐differences in gel electrophoresis (2D‐thiol‐DIGE) technique as initial approach to detect proteins with free cysteine residues, peptides containing the residues Cys 282 of creatine kinase and Cys 232 of alpha‐1 antitrypsin were identified as being alkylated by the chemical warfare agent sulfur mustard (SM). Both peptides might present potential biomarkers of SM exposure.